Recent Developments in Tandem White Organic Light-Emitting Diodes - Peng Xiao; Junhua Huang; Yicong Yu; Baiquan Liu (Molecules, 2019)
Tandem white organic light-emitting diodes (WOLEDs) are promising for the lighting and displays field since their current efficiency, external quantum efficiency and lifetime can be strikingly enhanced compared with single-unit devices. In this invited review, we have firstly described fundamental concepts of tandem device architectures and their use in WOLEDs. Then, we have summarized the state-of-the-art strategies to achieve high-performance tandem WOLEDs in recent years. Specifically, we have highlighted the developments in the four types of tandem WOLEDs (i.e., tandem fluorescent WOLEDs, tandem phosphorescent WOLEDs, tandem thermally activated delayed fluorescent WOLEDs, and tandem hybrid WOLEDs). Furthermore, we have introduced doping-free tandem WOLEDs. In the end, we have given an outlook for the future development of tandem WOLEDs.